A Comparative Study of John Dewey and Muhammad Iqbal as Educationist - Yusrat Hussain،Niaz Muhammad Aajiz، Muhammad Idrees (PJDOL, 2019)
A comparative study of Dewey and Iqbal as Educationists is based on scientific approach which combines findings of different scientific researches and is recognized as Meta- analysis. The fundamental principle in Meta-analysis is to search for a shared truth which may be found in good number of conceptually similar scientific researches.. The interviews of Heads of Education Departments may be considered the most valuable inputs of scholarly personalities.